Antidiabetic effects of isolated sterols from Ficus racemosa leaves1. Issue 44 (16th May 2015) - Kushwaha, Priya Singh; Raj, Vinit; Singh, Ashok K.; Keshari, Amit K.; Saraf, Shubhini A.; Mandal, Subhash C.; Yadav, Rajnish Kumar; Saha, Sudipta
<x xml:space="preserve">Abstract</x> Isolation and structure confirmation through NMR and MS. Antidiabetic and hypolipidemic activities using streptozotocin induced albino rats. Toxicological assessments. Mechanistic study to PPARγ through molecular docking.